RUANG LINGKUP MANAJEMEN PENDIDIKAN ISLAM - Yustia Rachma Fitriani; Sri Minarti (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The purpose of this study is to examine the scope and key components that define the field of Islamic education management We can see that management is. an ability or skill of activities that include arrangement, and institutions designed to facilitate the achievement of educational objectives with optimal effectiveness and efficiency.Proper management planning will result in a smooth running process. Educational management is directed toward shaping students' personalities in alignment with educational objectives, focusing on both the development and enhancement of learners according to established educational goals. This article aims to analyze and elaborate on the scope of Islamic education management. The study adopts a literature review approach to gather data, relying on the examination and analysis of various factual and credible reference sources in the form of qualitative data obtained from multiple scholarly articles.